Effects of Organotins on Crustaceans: Update and Perspectives - Vogt, Éverton L.; Model, Jorge F. A.; Vinagre, Anapaula S. (Frontiers in Endocrinology, 2018)
Organotins (OTs) are considered some of the most toxic chemicals introduced into aquatic environments by anthropogenic activities. They are widely used for agricultural and industrial purposes and as antifouling additives on boat hull’s paints. Even though the use of OTs was banned in 2008, elevated levels of OTs can still be detected in aquatic environments. OTs’ deleterious effects upon wildlife and experimental animals are well documented and include endocrine disruption, immunotoxicity, neurotoxicity, genotoxicity and metabolic dysfunction. Crustaceans are key members of zooplankton and benthonic communities and have vital roles in food chains, so the endocrine disrupting effects of TBT (Tributyltin) on crustaceans can affect other organisms. TBT can disrupt carbohydrate and lipid homeostasis of crustaceans by interacting with Retinoid X Receptor (RXR) and Crustacean Hyperglycaemic Hormone (CHH) signaling. Moreover, it can also interact with other nuclear receptors, disrupting MF (Metyl Farnesoate) and ecdysteroid signaling, thereby altering growth and sexual maturity, respectively. This compound also interferes in Cytochrome P450 system disrupting steroid synthesis and reproduction. Crustaceans are also important fisheries worldwide and its consumption can pose risks to human health. However, some questions remain unanswered. This mini review aims to update information about the effects of OTs on the metabolism, growth and reproduction of crustaceans, compare with known effects in mammals, as well as to point aspects that still needs to be addressed in future studies. Since both macro and microcrustaceans are good models to study the effects of sub lethal TBT contamination, novel studies should be developed using multibiomarkers and omics technology.